PENGGUNAAN SISTIM INFORMASI GEOGRAFIS UNTUK PEMETAAN KERAWANAN LONGSOR DI KABUPATEN PURWOREJO - Rahman, Abdur (Bumi Lestari, 2010)
Research of this case study was conducted in Purworejo Regency The Province of Central Java. in January 2008 . This Research aimed to map of landslide susceptibility in Purworejo Sub- further can be brought an action against by management which totally at area the happening and impact of landslide in topside and offside areas. This Research obtained Area of landslide which there are in Purworejo Sub-Province there are two district with very high level of susceptibility, 8 district have high level of susceptibility, 10 district have low level of susceptibility and two district have very low level of susceptibility. Landslide of area in Purworejo Sub-Province happened in north side and East side which domination with mountain has precipitous slope. Clay structure of land (silty clay) above impervious of rock in the form of Andesit, Breccia Formation, Dacite and Old Andesit formation and Bemelen, Peniron Formation.
Keywords: GIS; landslide susceptibility; management; impact